The effect of financial development on economic growth: a meta-analysis - Michiel Bijlsma; Clemens J. M. Kool; Marielle Non (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
Empirical studies on the finance-growth relationship show a wide range of estimated effects. We perform a meta-analysis on in total 551 estimates from 68 empirical studies that take private credit to GDP as a measure for financial development and distinguish between linear and logarithmic specifications. First, we find evidence of significantly positive publication bias in both the linear and log-linear specifications. This contrasts with findings in two other recent meta-studies, possibly due to a distortion introduced by their transformation procedure. Second, the logarithmic estimates give a robust significantly positive average effect of financial development on economic growth after correction for publication bias. In our preferred specification a 10 percent increase in credit to the private sector increases economic growth with 0.09 percentage points. For the linear estimates, no significant effect of credit to the private sector on economic growth is found on average. Over-all, the evidence points to a positive but decreasing effect of financial development on growth.
Keywords: 330; Financial development; economic growth; credit to the private sector; meta-analysis